PENGARUH EFFECTIVE TAX RATE, TUNNELING INCENTIVE DAN EXCHANGE RATE PADA KEPUTUSAN TRANSFER PRICING PERUSAHAAN ( STUDI EMPIRIS PADA PERUSAHAAN IDX 30 YANG TERDAFTAR PADA BURSA EFEK INDONESIA PERIODE 2020-2023 ) - Rumengan, Hutri Elisa Agnes; Karamoy, Herman; Weku, Priscillia (Universitas Sam Ratulangi, 2024)
This study aims to examine the effect of effective tax rate, tunneling incentive and exchange rate on corporate transfer pricing decisions. The data used in this study is secondary data in the form of annual financial statements obtained through the official website www.idx.co.id. The sampling technique used is purposive sampling so that 15 companies are obtained from 59 companies in the IDX 30 category listed on the Indonesia Stock Exchange for the 2020-2023 period and after the outlier method there are 35 samples from 60 samples included in the research sample. The analysis method used is quantitative analysis technique method with multiple regression analysis to see the effect of the independent variable on the dependent variable and the type of research used in this research is descriptive quantitative. The result shows that effective tax rate affects transfer pricing while tunneling incentive and exchange rate have no effect on transfer pricing.Keywords : Effective tax rate, Tunneling incentive, Exchange rate, Transfer pricing.